Sustainable ferrate oxidation: Reaction chemistry, mechanisms and removal of pollutants in wastewater. (1st December 2021) - Dar, Afzal Ahmed; Pan, Bao; Qin, Jiani; Zhu, Qiuhui; Lichtfouse, Eric; Usman, Muhammad; Wang, Chuanyi
Abstract: This review is intended to evaluate the use of ferrate (Fe(VI)), being a green coagulant, sustainable and reactive oxidant, to remove micro pollutants especially pharmaceutical pollutants in contaminated water. After a brief description of advanced oxidation processes, fundamental dimensions regarding the nature, reactivity, and chemistry of this oxidant are summarized. The degradation of contaminants by Fe(VI) involves several mechanisms and reactive agents which are critically evaluated. The efficiency and chemistry of Fe(VI) oxidation differs according to the reaction conditions and activation agent, such as soluble Fe(VI) processes, which involve Fe(VI), UV light, and electro-Fe(VI) oxidation. Fe(VI) application methods (including single dose, multiple doses, chitosan coating etc), and Fe(VI) with activating agents (including sulfite, thiosulfate, and UV) are also described to degrade the micro pollutants. Besides, application of Fe(VI) to remove pharmaceuticals in wastewater are intensely studied. Electrochemical prepared Fe(VI) has more wide application than wet oxidation method. Meanwhile, we elaborated Fe(VI) performance, limitations, and proposed innovative aspects to improve its stability, such as the generation of Fe(III), synergetic effects, nanopores entrapment, and nanopores capsules. This study provides conclusive direction for synergetic oxidative technique to degrade the micro pollutants. Graphical abstract: Image 1 Highlights: Recent advancements in ferrate's (Fe(VI)) remediation to degrade micro pollutants. Potential reactive agents to facilitate Fe(V)/Fe(IV) for more redox potential than Fe(VI). The degradation of micro pollutant is mediated by catalytic activities. Activation of Fe(VI) by UV was systematically reviewed.